The Impact Of Product Quality On Customer Loyalty Through Customer Satisfaction Among Generation Z Consumers Of Kopi Kenangan In Makassar City - Uhud Darmawan Natsir (International Journal of Education Management and Religion, 2026)
This study investigates the effect of product quality on customer loyalty with customer satisfaction serving as a mediating variable among Generation Z consumers of Kopi Kenangan in Makassar City. The study was motivated by the increasing competition within Indonesia’s coffee shop industry and the declining Top Brand Index of Kopi Kenangan despite its strong brand recognition among Generation Z consumers. Grounded in Consumer Behavior Theory and Expectancy Disconfirmation Theory, this research employed a quantitative explanatory approach to examine the relationships among product quality, customer satisfaction, and customer loyalty. Data were collected from 110 Generation Z consumers who had purchased Kopi Kenangan products at least three times within the previous two months. Respondents were selected using purposive sampling, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0.9.9. The measurement model demonstrated satisfactory validity and reliability, with all factor loadings exceeding 0.70, Average Variance Extracted (AVE) values above 0.50, and Composite Reliability values above 0.90. The structural model revealed that product quality has a positive and significant effect on customer satisfaction (β = 0.772, p < 0.001) and customer loyalty (β = 0.241, p = 0.009). Customer satisfaction also exerts a positive and significant influence on customer loyalty (β = 0.598, p < 0.001). Furthermore, mediation analysis confirmed that customer satisfaction partially mediates the relationship between product quality and customer loyalty (β = 0.462, p < 0.001), with a Variance Accounted For (VAF) value of 65.79%. These findings indicate that improving product quality enhances customer satisfaction, which subsequently strengthens customer loyalty. Therefore, maintaining consistent product quality and customer satisfaction is essential for sustaining long-term loyalty among Generation Z consumers in the highly competitive coffee shop industry.